The relationship between psychological capital and athlete burnout: the mediating relationship of coping strategies and the moderating relationship of perceived stress - Xiaomei Yu; Suxuan Xing; Yang Yang (BMC Psychology)
Abstract Background Athlete burnout represents a critical concern in sports psychology, significantly affecting athletes’ well-being and performance. This study examined the relationships among psychological capital, coping strategies, perceived stress, and athlete burnout. Methods A cross-sectional survey was conducted among 344 athletes, and data were analyzed using SPSS Statistics 25.0 and PROCESS Macro v4.1 for hierarchical stepwise regression and moderated mediation analysis. Control variables included age, gender, sport type, and competitive experience. Results The results revealed that psychological capital negatively associated with burnout both directly ( $$β$$ β = -0.539, p < 0.01) and indirectly (a*b = -0.803, p < 0.01) through coping strategies. Furthermore, perceived stress influenced both the relationship between psychological capital and coping strategies and the indirect effect of psychological capital on burnout via coping strategies. Notably, under high-stress conditions, the negative association of psychological capital was more pronounced, with a more substantial indirect effect compared to low-stress conditions ( $$β$$ β = -1.020, p < .01 vs. $$β$$ β = -0.299, p < .01). Conclusions These findings underscore the importance of cultivating psychological resources and adaptive coping mechanisms to mitigate burnout, offering valuable insights for targeted interventions aimed at enhancing the well-being of athletes, particularly those experiencing elevated stress levels.